THE ROLE OF MADRASAH CULTURE IN FORMATION SELF-CONCEPT OF RELIGIOUS STUDENTS - Subiyantoro, Subiyantoro (JURNAL JPSD (Jurnal Pendidikan Sekolah Dasar), 2015)
This study aims to: (1) Determine how the socio-cultural-educational Madrasah Aliyah, in city sub-district, city districts, and the Municipality of Yogyakarta. (2) Determine how buildsthe self-concept of students in the process of religious education in Madrasah Aliyah in the Sub-District city, districts city, and in the Municipality of Yogyakarta. (3) Determine how the important of culture Madrasah, in buildsthe self-concept religious Madrasah Aliyah students in the Sub-districts city, districts city, and in the Municipality of Yogyakarta.The results shows that (1) Images of the madrasah culture "material culture" of third-MAN in the state programmed, organized, neat, clean, and some have "shade/green", because of the power figures are consistently portrayed by Principals or Head of Administration. Portrait madrasah culture "culture activities" of religious MAN was almost the same third tadarusin the morning, dhuhur congregation prayers, Friday prayers, Quran reading guidance. There are two supplements that add madrasah activity, madrassa adding that the self-development activities "Missionary Candidate" and "Saturday Islamic School Sunday" (Wisdom). What distinguishes the three madrasas in this field is the intensity and istiqomah in guarding program. (2) in the formation of students self-concept of religiosity is the third MAN, not just rely on PAI learning in the classroom, but they also build activities outside the classroom, although the "spirit" of the managers "equal" that is sought to enable the students to have high religiosity, but MAN municipality has a higher spirit. (3) in terms of the role of culture in fostering religiosity madrassa students, the existence of an identity Principals or other figure, very involved, and the presence of factors "habituation" and activities "istiqomah". In municipality,MAN environment teacher more progressive, critical and reactive. It is a hallmark of positive bias control "vision". In an environment where getting to the bottom (at the district and sub-district town), and control the character look even weaker. Besides, that "Work Ethics" Municipality MAN also more awake than the other two MAN.